A novel label-free fluorescence strategy for methyltransferase activity assay based on dsDNA-templated copper nanoparticles coupled with an endonuclease-assisted signal transduction system. Issue 4 (14th January 2016) - Lai, Q. Q.; Liu, M. D.; Gu, C. C.; Nie, H. G.; Xu, X. J.; Li, Z. H.; Yang, Z.; Huang, S. M.
Abstract : A novel label-free fluorescence method by coupling dsDNA-templated CuNPs with endonuclease-assisted signal transduction has been developed for methyltransferase activity assay. Abstract : Evaluating DNA methyltransferase (MTase) activity has received considerable attention due to its significance in the fields of early cancer clinical diagnostics and drug discovery. Herein, we proposed a novel label-free fluorescence method for MTase activity assay by coupling double-stranded DNA (dsDNA)-templated copper nanoparticles (CuNPs) with an endonuclease-assisted signal transduction system. In this strategy, dsDNA molecules were first methylated by DNA adenine methylation (Dam) MTase and then cleaved by the methylation-sensitive restriction endonuclease DpnI. The cleaved DNA fragments could not act as efficient templates for the formation of fluorescent CuNPs and thus no fluorescence signal was produced. Under optimized experimental conditions, the developed strategy exhibited a sensitive fluorescence response to Dam MTase activity. This strategy was also demonstrated to provide an excellent platform to the inhibitor screening for Dam MTase. These results demonstrated the great potential for the practical applications of the proposed strategy for Dam MTase activity assay.